Experiences from a Touch-Based Interaction and Digitally Enhanced Meal-Delivery Service for the Elderly. (17th July 2008) - Isomursu, Minna; Häikiö, Juha; Wallin, Arto; Ailisto, Heikki
Abstract : This paper reports the results of a field experiment where home-dwelling elderly people used a mobile technology-based service to interact with a home care service to order meals to be delivered to their homes. The primary research focus was on examining the suitability of touch-based interaction in the everyday life activities of elderly users. The eight-week experiment took place in the autumn of 2006. The findings are based primarily on user experience and on the socioeconomic analysis done from the data collected before, during, and after the experiment. The results show that touch-based interaction was easy to learn and adopt, and that the users were able to successfully use it regardless of their physical or cognitive weaknesses. However, the socioeconomic value of the service was questionable. The paper also summarises methodological issues and findings related to user experience evaluation in an experimental setting.